Laryngeal cancer, risk factors, symptoms and treatment - Besim Boçi; Albana Çuko (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2020)
The objective of this study is to identify trends in demographics, symptoms and treatment of laryngeal cancer and to analyze risk factors contributing to the emergence of this cancer. Review of 679 cases with laryngeal cancer diagnosed between the years 2002 and 2011 in ENT SERVICE in University Hospital Center "Mother Teresa". Analysis of these case records addressed demographics, risk factors and treatment for cases according to stage, site and TNM classifications. In all cases, their diagnosis has been confirmed by histopathological studies.